Creative education: an analytical reading of the concept and requirements - Boumelkahel, Linda (Journal of Human Sciences, 2022)
This article aims to explain the importance of Creative education as a necessity of modern education.Focusing on the foundations of the creative school management, the creative classroom management; and the creative curriculum, these are foundations that help in developing the creative abilities of learners; And training them in ways to develop their creative thinking in solving the various problems that interact with them to keep pace with most of the changes taking place in their external environment.